Pengaruh Tingkat Pengangguran Terbuka dan Inflasi Terhadap Pertumbuhan Ekonomi di Provinsi Lampung (Jurnal Kendali Akuntansi, 2023)
This study aims to analyze the effect of the open unemployment rate and inflation on economic growth in Lampung Province. The data used in this study covers the period from 2007 to 2021. The results show that the open unemployment rate has a significant negative effect on economic growth in Lampung Province. A high unemployment rate indicates a low level of labor involvement in economic activity, which has an impact on overall economic performance.